ChemInform Abstract: Auxiliary‐Directed Pd‐Catalyzed γ‐C(sp3)—H Bond Activation of α‐Aminobutanoic Acid Derivatives. Issue 18 (April 2016) - Pasunooti, Kalyan Kumar; Banerjee, Biplab; Yap, Terence; Jiang, Yaojia; Liu, Chuan‐Fa
Abstract: A new bidentate auxiliary derived from isoxazole‐3‐carboxamide, when placed on a primary amine compound, directs Pd‐catalyzed activation of inert γ‐C(sp 3 )—H bonds for C—C bond formation.